2017
DOI: 10.3390/su9122360
|View full text |Cite
|
Sign up to set email alerts
|

Coordinating a Two-Echelon Supply Chain under Carbon Tax

Abstract: Abstract:In this paper, we study the impact of carbon tax on carbon emission and retail price in a two-echelon supply chain consisting of a manufacturer and a retailer. Specifically, by adopting two types of contracts, i.e., the modified wholesale price (MW) and the modified cost-sharing contract (MS), supply chain coordination is achieved, which promotes the supply chain efficiency. Our study shows that: (1) with the increase of carbon tax, both the optimal emission reduction level and the optimal retail pric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Chen and Hao [15] studied the impacts of carbon tax policy on the sustainable pricing and production policies of two competing firms and showed that a firm obtains a larger carbon emissions reduction percentage if they undertake a higher carbon tax. Yu and Han [16] investigated the impacts of carbon tax policy on product retail price and total carbon emission in a supply chain with a manufacturer and a retailer and designed two contracts to coordinate the supply chain. Wang et al [17] studied the optimal production decisions of new and remanufactured products under carbon tax policy and found that manufacturers can offset the cannibalization and curb carbon emissions via adopting low-carbon emission technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Chen and Hao [15] studied the impacts of carbon tax policy on the sustainable pricing and production policies of two competing firms and showed that a firm obtains a larger carbon emissions reduction percentage if they undertake a higher carbon tax. Yu and Han [16] investigated the impacts of carbon tax policy on product retail price and total carbon emission in a supply chain with a manufacturer and a retailer and designed two contracts to coordinate the supply chain. Wang et al [17] studied the optimal production decisions of new and remanufactured products under carbon tax policy and found that manufacturers can offset the cannibalization and curb carbon emissions via adopting low-carbon emission technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similarly, the Chinese government has provided financial support to encourage consumers to buy new low-energy vehicles since 2015, and has also encouraged firms to offer green products [8]. Second, internal funds (e.g., greening cost-sharing between the members of a supply chain) is another method that can help firms to switch to the manufacture of green products [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…This paper referred to the environmental impact of enterprises in the process of the production and circulation of products [48]. Similar to the research on measuring environmental benefits through total carbon emissions [49][50][51][52], this study assumed that the utility function of an environmental benefits objective is the product of the greening level and market demand, which is:…”
Section: Model Hypothesesmentioning
confidence: 99%